Neural Prosthetics: Advancements and Ethical Consideration in Brain-Computer Interfaces - Yasaman Mohammadi; Mohammad Hossein Morowvat (Shiraz University of Medical Sciences, 2023)
Neural prosthetics employ different signals, such as chemical or electrical signals from the human nervous system, for stimulating or restoring the capabilities of injured people or different disease conditions (1). They are artificial extensions of the body that repair or fortify the human nervous system after various injuries or diseases (2).From ancient times, the study of neural systems has been a subject of fascination. Significant progress has been made in our understanding of neural systems, from the ancient understanding of the role of the brain in the body to today's research on artificial intelligence. Three main types of neural systems have been identified today: sensory, motor, and associative (3). These systems work together to let us perceive, process, and react to the world around us.The approach helps patients with various diseases, and implanting neural chips in the brain, is encouraging. These chips can monitor brain activity and relax symptoms such as tremors, seizures, and depression (4, 5). However, before widespread implementation, there is a need to address ethical concerns and potential risks.